2022
DOI: 10.3390/foods11030282
|View full text |Cite
|
Sign up to set email alerts
|

Role of Flaxseed Gum and Whey Protein Microparticles in Formulating Low-Fat Model Mayonnaises

Abstract: Flaxseed gum (FG) and whey protein microparticles (WPMs) were used to substitute fats in model mayonnaises. WPMs were prepared by grinding the heat-set whey protein gel containing 10 mM CaCl2 into small particles (10–20 µm). Then, 3 × 4 low-fat model mayonnaises were prepared by varying FG (0.3, 0.6, 0.9 wt%) and WPM (0, 8, 16, 24 wt%) concentrations. The effect of the addition of FG and WPMs on rheology, instrumental texture and sensory texture and their correlations were investigated. The results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…A maximum hardness and dynamic moduli was obtained at near neutral pH (6.8) due to combined effect of electrostatic and disulfide bonds giving higher toughness to SGWP than SG1 and control hydrogel (Tang et al., 1995). A similar correlation between rheological and textural parameters of hydrogels using Pearson's matrix has also been reported by other workers (Khubber et al., 2021; Li et al., 2022; Yang et al., 2022).…”
Section: Resultssupporting
confidence: 88%
“…A maximum hardness and dynamic moduli was obtained at near neutral pH (6.8) due to combined effect of electrostatic and disulfide bonds giving higher toughness to SGWP than SG1 and control hydrogel (Tang et al., 1995). A similar correlation between rheological and textural parameters of hydrogels using Pearson's matrix has also been reported by other workers (Khubber et al., 2021; Li et al., 2022; Yang et al., 2022).…”
Section: Resultssupporting
confidence: 88%
“…Although there have been some studies about the characterization of flaxseed mucilage (FM; Akl et al, 2020;Pohjanheimo et al, 2006) and Plantago Psyllium mucilage (PM; Wärnberg et al, 2009;Souza et al, 2020;Yang et al, 2022;El-Sayed et al, 2014), there are no reports that discussed the rheological behavior of mucilages in detail and applied them as fat replacers together in cookies or even other products. According to the beneficial effects of FM and PM on health, this study provides a complete overview of the FM and PM extraction and rheological properties of them as fat mimics on physicochemical, textural, and sensory properties of low-fat cookies.…”
Section: Introductionmentioning
confidence: 99%
“…The FM inclusion enhanced the survival of the probiotic bacteria, improved the texture, and increased the overall sensory quality of the cheese. Another study showed the potential of FG and whey protein microparticles (WPMs) as fat substitutes in model mayonnaises [ 45 ]. Both FG and WPMs improved the textural properties (e.g., adhesiveness, cohesiveness, hardness, and consistency), rheological properties (e.g., storage modulus and viscosity), and kinetic stability of model mayonnaises; this effect was largely ascribed to the inclusion of FG, which likely formed an entangled 3D network.…”
Section: Food Applications Of Fm/fgmentioning
confidence: 99%